Implementasi Sistem Informasi Desa Berbasis Web Menggunakan OpenSID di Desa Ngraket Kecamatan Balong Kabupaten Ponorogo - Candra Pamungkas; Nur Ratif Agustina; Musthofa Nur Fikri; Ari Kurniawan (Yayasan Literasi Sains Indonesia, 2024)
The Village Information System is an integral part of the implementation of the Village Law. Village Law Article 86 concerning Village Development Information Systems and Rural Area Development clearly requires that villages have the right to access information through information systems developed by the Regency or City Regional Government. Together with the rapid development of technology, the need for fast, accurate, easy and practical data processing has become a demand. This also applies to data management in village government institutions, where each village is required to provide the best service to the community in various fields such as writing letters, population data collection, and other needs related to services at the village office. However, most of the service processes still use conventional methods. Therefore, we propose the use of a web-based community service application in Ngraket Village. This application is designed using a web platform so that it can be accessed online, allowing the people of Ngraket Village to enjoy Village services more quickly and easily. The implementation of this Village website must be carried out actively and the content must be in accordance with the menu available on the website. The implication of implementing a website-based village information system is to increase transparency, community participation and information accessibility. With this application, it is hoped that the quality of the service process to the people of Ngraket Village can increase significantly.